2008
DOI: 10.1111/j.1474-9726.2008.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases levels of endogenous amyloid‐β peptides secreted from primary chick brain neurons

Abstract: SummaryOxidative damage is associated with Alzheimer's disease and mild cognitive impairment, but its relationship to the development of neuropathological lesions involving accumulation of amyloid-β β β β (Aβ β β β ) peptides and hyperphosphorylated tau protein remains poorly understood. We show that inducing oxidative stress in primary chick brain neurons by exposure to sublethal doses of H 2 O 2 increases levels of total secreted endogenous Aβ β β β by 2.4-fold after 20 h. This occurs in the absence of chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
2
29
0
1
Order By: Relevance
“…8,9 For instance, the accumulation of Ab in primary neurons could induce oxidative stress. 10 Ab accelerates additional inflammatory pathways by activation of cyclooxygenase-2 in astrocytes via an interaction with interleukin-1b, tumor necrosis factor-a, and a nuclear factor-jB (NF-jB) mechanism in the rat brain. 11 Moreover, evidence also indicates that Ab-induced neurotoxicity is associated with the PI3K/Akt/GSK-3b signaling pathway.…”
mentioning
confidence: 99%
“…8,9 For instance, the accumulation of Ab in primary neurons could induce oxidative stress. 10 Ab accelerates additional inflammatory pathways by activation of cyclooxygenase-2 in astrocytes via an interaction with interleukin-1b, tumor necrosis factor-a, and a nuclear factor-jB (NF-jB) mechanism in the rat brain. 11 Moreover, evidence also indicates that Ab-induced neurotoxicity is associated with the PI3K/Akt/GSK-3b signaling pathway.…”
mentioning
confidence: 99%
“…Several studies show that oxidative stress biomarkers are elevated in the early stages of AD, suggesting that this is an early event in the development of AD pathology (Nunomura et al, 2001;Lovell and Markesbery, 2007). Oxidative stress and Ab are interlinked, since Ab promotes oxidative stress (Cutler et al, 2004;Jhoo et al, 2004;Tabner et al, 2005), which, in turn, enhances production of Ab (Misonou et al, 2000;Paola et al, 2000;Tamagno et al, 2002Tamagno et al, , 2005Tamagno et al, , 2008Tong et al, 2005;Goldsbury et al, 2008;Shen et al, 2008). Moreover, several antioxidants protect neurons from toxicity induced by Ab (Cutler et al, 2004;Jhoo et al, 2004;Ono et al, 2006) and suppress Ab levels in mouse brain (Sung et al, 2004).…”
mentioning
confidence: 99%
“…This oxidative stress precedes the appearance of amyloid plaques and β-amyloid might be generated as a compensatory response by neurons to attenuate this stress (Goldsbury et al, 2008). Actually, the decrease of the mitochondrial respiration associated with increased activity of the complex III seems to appear at low physiological concentrations of β-amyloid (Rhein et al, 2009) and β-amyloid peptide has been found oxidized in the amyloid plaques (Hureau and Faller, 2009).…”
Section: β-Amyloid Interacts With Reactive Oxygen Species Productionmentioning
confidence: 99%